Analisis Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Industri Makanan dan Minuman - Astuti, Thesa Puji; Hanim, Wasifah; Sugihyanto, Toto (Universitas Muhammadiyah Metro, 2023)
Price to Book Value is very important for the company because a healthy company will produce a good image for the company both internally and externally. The purpose of this study aims to determine the effect of Company Growth, Price Earning Ratio, Leverage, Profitability on Price to Book Value The research object is all manufacturing companies in the food and beverage sub-sector on the Indonesia Stock Exchange, the analysis period is 2019. The number of companies is 34, consisting of 26 (twenty six) food companies and 8 (eight) beverage companies, all as samples study. The method used is multiple linear regression using Cross Section data. Based on the results of the analysis concluded that the company's growth, leverage, profitability have a positive and significant effect on firm value. Means the increasing growth of the company, Leverage, Profitability will increase the value of the company. While the Price Earning Ratio is not significant to the value of the company.